Promoting Asian Economic Development by Designing Culturally Conscious Alternative Dispute Resolution (ADR) - Alina, Baimoldayeva; Malik , Zia-Ud-Din (Journal of Legal Studies, 2022)
It is critical to develop an Asian model of alternative conflict resolution that takes Asian traditions into account. Simply adopting Western standards will be less likely to accommodate Asians’ distinctive approach to conflict resolution. If international business mediation or arbitration is sensitive to cultural requirements and expectations, culture-related issues may be avoided.